PERLINDUNGAN HUKUM TERHADAP KEBOCORAN DATA NASABAH DITINJAU DARI UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN - Bhoki, Aurelya; Aloysius, Sukardan; Dju Bire, Chatryen M (Petitum Law Journal, 2024)
A bank is defined as an institution that protects customer funds, not only protecting but also having the obligation to maintain the confidentiality of its customer funds and data from parties who can harm and misuse customers personal data. Leaks are a problem that often occurs in society, even though it haas been regulated in however, it occur make people worry and think about why the factors that cause customer data leaks and to analyze legal protection efforts where data is leaked. The research methode used is normative research, using a statutory, case and context approach. The results of the research are to reveal the factors that cause data leaks and forms of legal protection efforts for customers whose data is leaked.